Changing perspectives in the history of science : (Heinemann Educational, 1973)
The first is to bring together a number of approaches to the history of science which have emerged in recent years and to make available essays by leading scholars in the field which reflect these approaches. The second is to honour Joseph Needham, a scholar whose work has booth reflected and inspired interest, research topics, and geographical and historiographic viewpoints which extend and deepen the discipline.